Ferumoxytol-enhanced cardiovascular magnetic resonance detection of early stage acute myocarditis - Tada, Yuko (J Cardiovasc Magn Reson, 2019)
BACKGROUND: The diagnostic utility of cardiovascular magnetic resonance (CMR) is limited during the early stages of myocarditis. This study examined whether ferumoxytol-enhanced CMR (FE-CMR) could detect an earlier stage of acute myocarditis compared to gadolinium-enhanced CMR. METHODS: Lewis rats were induced to develop autoimmune myocarditis. CMR (3 T, GE Signa) was performed at the early- (day 14, n = 7) and the peak-phase (day 21, n = 8) of myocardial inflammation. FE-CMR was evaluated as % myocardial dephasing signal loss on gradient echo images at 6 and 24 h (6 h- & 24 h-FE-CMR) following the administration of ferumoxytol (300μmolFe/kg). Pre- and post-contrast T2* mapping was also performed. Early (EGE) and late (LGE) gadolinium enhancement was obtained after the administration of gadolinium-DTPA (0.5 mmol/kg) on day 14 and 21. Healthy rats were used as control (n = 6). RESULTS: Left ventricular ejection fraction (LVEF) was preserved at day 14 with inflammatory cells but no fibrosis seen on histology. EGE and LGE at day 14 both showed limited myocardial enhancement (EGE: 11.7 ± 15.5%; LGE: 8.7 ± 8.7%; both p = ns vs. controls). In contrast, 6 h-FE-CMR detected extensive myocardial signal loss (33.2 ± 15.0%, p = 0.02 vs. EGE and p < 0.01 vs. LGE). At day 21, LVEF became significantly decreased (47.4 ± 16.4% vs control: 66.2 ± 6.1%, p < 0.01) with now extensive myocardial involvement detected on EGE, LGE, and 6 h-FE-CMR (41.6 ± 18.2% of LV). T2* mapping also detected myocardial uptake of ferumoxytol both at day 14 (6 h R2* = 299 ± 112 s(− 1)vs control: 125 ± 26 s(− 1), p < 0.01) and day 21 (564 ± 562 s(− 1), p < 0.01 vs control). Notably, the myocardium at peak-phase myocarditis also showed significantly higher pre-contrast T2* (27 ± 5 ms vs control: 16 ± 1 ms, p < 0.001), and the extent of myocardial necrosis had a strong positive correlation with T2* (r = 0.86, p < 0.001). CONCLUSIONS: FE-CMR acquired at 6 h enhance detection of early stages of myocarditis before development of necrosis or fibrosis, which could potentially enable appropriate therapeutic intervention.